2020
DOI: 10.1016/s0140-6736(20)30251-8
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterisation and epidemiology of 2019 novel coronavirus: implications for virus origins and receptor binding

Abstract: Background In late December, 2019, patients presenting with viral pneumonia due to an unidentified microbial agent were reported in Wuhan, China. A novel coronavirus was subsequently identified as the causative pathogen, provisionally named 2019 novel coronavirus (2019-nCoV). As of Jan 26, 2020, more than 2000 cases of 2019-nCoV infection have been confirmed, most of which involved people living in or visiting Wuhan, and human-to-human transmission has been confirmed. MethodsWe did next-generation sequencing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

111
10,958
2
525

Year Published

2020
2020
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10,993 publications
(12,021 citation statements)
references
References 37 publications
111
10,958
2
525
Order By: Relevance
“…Of these bat species, the first three can be found in the province of Hubei (source: www. This produced the highest identity to the same isolate that Lu and coworkers had identified (Lu et al 2020), demonstrating that an analysis of 253 nucleotides directly upstream of the start codon of the polycystronic messenger suffices to identify genetic relationships between Sarbecovirus species. A number of whole genome Sarbecovirus sequences isolated from these bats and other bat species were selected and their 5'-flank was compared to that of 2019_nCoV (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…Of these bat species, the first three can be found in the province of Hubei (source: www. This produced the highest identity to the same isolate that Lu and coworkers had identified (Lu et al 2020), demonstrating that an analysis of 253 nucleotides directly upstream of the start codon of the polycystronic messenger suffices to identify genetic relationships between Sarbecovirus species. A number of whole genome Sarbecovirus sequences isolated from these bats and other bat species were selected and their 5'-flank was compared to that of 2019_nCoV (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…12 , 14 The spike protein, composed of S1 and S2 domain, was crucial to the determine host tropism and transmission capacity through the mediation of receptor binding and membrane fusion. 12 Among these, the S2 subunit of the 2019-nCoV is highly conserved and has a 99% identity with that of SARS-CoV. 12 The receptor-binding domain, is commonly located in the C-terminal domain of S1 to directly contact the human receptor.…”
Section: Genomic and Structurementioning
confidence: 99%
“…12 Among these, the S2 subunit of the 2019-nCoV is highly conserved and has a 99% identity with that of SARS-CoV. 12 The receptor-binding domain, is commonly located in the C-terminal domain of S1 to directly contact the human receptor. Although, the S1 domain of the 2019-nCoV only has approximately 70% identity with SARS-CoV, homology modelling revealed that the 2019-nCoV has a similar receptor-binding domain structure to that of SARS-CoV.…”
Section: Genomic and Structurementioning
confidence: 99%
“…5 A novel 2019 coronavirus (SARS-CoV-2) belongs to the Betacoronavirus genus of the Coronaviridae family. It shares more than 79% homology with SARS-CoV, 6 and causes mild to severe disease, with fatal bilateral viral pneumonia described in humans. 7 ,8 It is referred to as a novel coronavirus because it has not previously been observed in the human population.…”
Section: Introductionmentioning
confidence: 99%